Early Childhood Education Monitoring Information System (PAUD) Using Design Thinking Approach - Fiarni, Cut; Yoanata, Yosi; Maranatha, Immanuel Fellita (Department of Informatics Universitas Islam Indonesia, 2024)
PAUD Permata Tunas Daud is one of the early childhood education schools in East Java. As an early childhood education institution, communication between the school and parents regarding monitoring progress of students is very much needed; that's why Permata Tunas Daud PAUD implements two-way communication with a communication book run every week. However, physical books that frequently change hands carry a risk of loss and damage. In addition, the existing document form contains only some of the information one wishes to receive and convey. Therefore, this study aims to develop a system to help share teachers' knowledge with parents. This research used the waterfall method for software development and design thinking for problem collection. After the analysis, a solution for making an information system is determined with several features, such as an assessment element carried out by the teacher; this feature facilitates the teacher to create information on child development, which will later be displayed to parents. The system also provides an announcement feature for teachers to share knowledge with parents to support children's growth. After the software is developed, the system will be tested with two testing methods, namely black box testing and testing the user with User Acceptance Testing (UAT). Based on the UAT that has been carried out, it is found that each test has produced a value greater than or equal to 80%, so it can be concluded that the system succeeded in getting good scores from all aspects and for each user.